The urgency of implementation SAK EP in replacing SAK ETAP in savings and loan cooperatives - Asmara, Rina Yuliastuty; Kamil, Islamiah; Ariani, Meiliyah (Privietlab, 2024)
Savings and Loans Cooperatives (KSP) play an important role in the community’s economy, especially in providing financial access to their members. However, in man- aging their finances, many KSPs still use the Entity Without Public Accountability Financial Accounting System (SAK ETAP). This Community Service aims to ana- lyze the urgency of implementing Financial Accounting Standards for Fund Manage- ment Entities (SAK EP) as a replacement for SAK ETAP in the KSP context. The community service method is carried out through socialization, training and direct assistance to KSP administrators and members in implementing SAK EP. Com- munity Service Results show that the implementation of SAK EP in KSP provides significant benefits, including increased transparency, accountability and reliability of financial information. The use of SAK EP also helps KSP in meeting regulatory requirements and increasing the trust of members and external parties such as banks and the government. Apart from that, this community service also strengthens un- derstanding and accounting skills for KSP administrators and members, which in turn can improve the quality of financial management and overall KSP business growth. This community service emphasizes the urgency of implementing SAK EP in replacing SAK ETAP in KSP as an important step towards better financial gov- ernance, which has a positive impact on the economic growth of society as a whole.